Patient Advocates' Perspectives on the Care of Sexual Assault Survivors in Chicago-Area Emergency Departments. (February 2023) - Chalmers, Kristen D.; Parameswaran, Ramya; Dussault, Nicole E.; Farnan, Jeanne M.; Oyola, Sonia; Carter, Keme
Emergency departments (EDs) providing care and forensic examinations for sexual assault (SA) survivors are often supported by SA patient advocates. This study explored advocates' perspectives regarding problems and potential solutions in SA patient care through a focus group with 12 advocates. Thematic analysis identified two major themes: provider–patient interactions and ED–hospital systems. Challenging aspects of provider–patient interactions included (a) provider attitudes and (b) disempowering behaviors. Within ED–hospital systems, themes included time constraints, efficiencies, and hospital preparation. Advocates surveyed were optimistic about an increased presence of SA nurse examiners and enhanced protocols and provider training to improve survivors' experiences.